2015
DOI: 10.1002/ange.201504784
|View full text |Cite
|
Sign up to set email alerts
|

Rattling in the Quadruple Perovskite CuCu3V4O12

Abstract: Of particular interest is ap eculiar motion of guest atoms or ions confined to nanospace in cage compounds, called rattling.W hile rattling provides unexplored physical properties through the guest-host interactions,ithas only been observed in av ery limited class of materials.H erein, we introduce an A-site-ordered quadruple perovskite, CuCu 3 V 4 O 12 ,a sanew family of cage compounds.T his novel AA' 3 B 4 O 12 -type perovskite has been obtained by ah ighpressure synthesis technique and structurally characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
(50 reference statements)
1
8
0
Order By: Relevance
“…Our structural analysis indicates that Na1 has 12 equidistant Na1− O bonds (2.701(18) Å), whereas Na2 has four short (2.552(17) Å), four medium (2.778(17) Å), and four long (2.916(17) Å) bonds (Figure 2d). The available space of Na1 and Na2 is estimated by calculating 9,24,34,35,38 where d is the Na−O bond length and r(O 2− ) refers to the ionic radius of O 2− (=1.4 Å). 39 This yielded d cage = 1.301 Å for Na1 and 1.152, 1.378, and 1.516 Å for Na2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our structural analysis indicates that Na1 has 12 equidistant Na1− O bonds (2.701(18) Å), whereas Na2 has four short (2.552(17) Å), four medium (2.778(17) Å), and four long (2.916(17) Å) bonds (Figure 2d). The available space of Na1 and Na2 is estimated by calculating 9,24,34,35,38 where d is the Na−O bond length and r(O 2− ) refers to the ionic radius of O 2− (=1.4 Å). 39 This yielded d cage = 1.301 Å for Na1 and 1.152, 1.378, and 1.516 Å for Na2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, Tanaka et al reported several quadruple perovskite oxides, ACu 3 V 4 O 12 (A = Mn, Cu). 23,24 In general, the A′ ions in AA′ 3 B 4 O 12 are Jahn−Teller active transition metals (e.g., Cu 2+ and Mn 3+ ), and extensive BO 6 octahedral tilting permits square-planar A′O 4 coordination. 25 The resultant A site is 12-fold coordinated typically occupied by large alkaline earth metals (e.g., La), but when it is occupied by small transition metal ions, a rattling phenomenon emerges, as seen from a large atomic displacement parameter (ADP) and Einstein-like specific heat.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced t can cause structural distortion and thus large spontaneous electrical polarization (P S ) in noncentrosymmetric materials , 58,59 while the transition-metal-rich lattices lead to robust magnetic interplays and thus magnetoelectric effect. 15,28,51 [53][54][55] This list can be even longer. However, these exotic perovskites are thermodynamically metastable and need to be prepared at high-pressure (usually above 6 GPa) and temperature (HPT).…”
Section: Introductionmentioning
confidence: 99%
“…in icosahedral coordination. [19][20][21][22][23] It was recently reported that the A-sites also tolerate a wide range of ions such as Mn 2+ and Cu + , [24][25][26] in addition to smaller rare-earth metal ions (Y 3+ , Lu 3+ , etc.). 27 The Cd ions are also incorporated into A-sites in the quadruple perovskites such as CdCu 3 Ti 4 O 12 , 28,29 31 and CdMn 7 O 12 .…”
Section: Introductionmentioning
confidence: 99%